2009
DOI: 10.3758/lb.37.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Preference for 50% reinforcement over 75% reinforcement by pigeons

Abstract: When animals appear to behave maladaptively, it may inform us about the processes underlying their behavior. Hungry animals generally prefer alternatives that provide more reinforcement or a higher probability of reinforcement. Thus, when Kendall (1974) reported that pigeons p prefered an alternative that provided food 50% of the time over one that provided food 100% of the time, the result was surprising. In Kendall's procedure, choice of one alternative led to a white-lit key and reinforcement 100% of the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
141
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(155 citation statements)
references
References 18 publications
(33 reference statements)
11
141
0
Order By: Relevance
“…According to information theory, reducing the probability of reinforcement from 50% (in Gipson et al, 2009) to 20% in the present experiment should have reduced the information provided by the discriminative stimuli, because signals for reinforcement and nonreinforcement should be most informative when without them there would be maximum ambiguity (i.e., 50% reinforcement). Thus, reducing the overall probability of reinforcement should have reduced the preference for the alternative leading to the discriminative stimuli.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…According to information theory, reducing the probability of reinforcement from 50% (in Gipson et al, 2009) to 20% in the present experiment should have reduced the information provided by the discriminative stimuli, because signals for reinforcement and nonreinforcement should be most informative when without them there would be maximum ambiguity (i.e., 50% reinforcement). Thus, reducing the overall probability of reinforcement should have reduced the preference for the alternative leading to the discriminative stimuli.…”
Section: Discussionmentioning
confidence: 83%
“…The experiment was conducted in a BRS/LVE (Laurel, MD) sound-attenuating standard operant test chamber (see Gipson et al, 2009, for details).…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals preferred to observe stimuli that predicted whether reinforcement would or would not be delivered over cues that were non-informative. Finally, the Gipson et al (2009) experiment showed that pigeons strongly preferred to peck a key that led to only 50% reinforcement over a key that led to 75% reinforcement because the 50% key led to cues consistently predictive of reinforcement and non-reinforcement and the 75% key did not.…”
Section: Informantmentioning
confidence: 95%
“…Even more striking is a recent report by Gipson, Alessandri, Miller, and Zentall (2009;Experiment 2; also see Zentall, 2011). Pigeons chose between left and right white keys, with pecks on one key turning the key red on a random 50% of the trials and green on the other 50% of the trials.…”
Section: Figure 1 a Rhesus Monkey Is Shown Looking Down Tubes One Omentioning
confidence: 99%